A Comparative Clinical Trial on Curcuma angustifolia Roxb. Extract Versus Omeprazole in the Management of Hyperacidity W.S.R to Amlapitta Treatment - Prof.(Dr.) Rikal Kailas; Prof.(Dr.) Prasanna Sriram Mathad; Dr.Kavitha Rikal (The Bioscan, 2026)
Peoples in developing and developed countries of contemporary era demands modern lifestyle which provides number of facilities makes the ways of daily routine much easier. But many of the modern lifestyle patterns adversely affect health physically, psychologically and socially. Especially modern diet style adopted by the people of present nuclear family is such an example for the cause of many of the gastro intestinal disorders. Hyperacidity is major aftereffects of such an unhealthy dietary healthy behaviour. The present research work is a clinical trial to evaluate the efficacy of Curcuma angustifolia Roxb. Extract prepared using Ayurvedic classical methods versus scientifically worldwide accepted stand drug of choice Omeprazole in the management of Hyperacidity in the point of view with clinical condition Amlapitta mentioned in Ayurvedic texts of Indian traditional medicine.